2022
DOI: 10.3389/fcimb.2022.807218
|View full text |Cite
|
Sign up to set email alerts
|

Promising Anti-Biofilm Agents and Phagocytes Enhancers for the Treatment of Candida albicans Biofilm–Associated Infections

Abstract: Little is known about the interactions among phagocytes and antifungal agents and the antifungal immunomodulatory activities on Candida species biofilms. Here, inhibition of C. albicans biofilms and the interactions among biofilms and phagocytes alone or in combination with essential oils, biological, and chemical agents, or fluconazole were investigated. Biofilm formation by a panel of 28 C. albicans clinical isolates from hospitalized patients, birds, and cattle was tested. The anti-biofilm activities of cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
(70 reference statements)
1
12
0
Order By: Relevance
“…In addition, the MBEC values of natural products and antifungals were up to 8 times and 4 times higher than their MFC values, respectively. Tese results showed that the bioflm was more resistant to antimicrobial agents than planktonic cells, and this could be explained by the limited difusion of antimicrobial agents through the bioflm matrix or the lower growth rate of cells in the bioflm [6,36]. Tese results corroborated those reported earlier [14,24].…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the MBEC values of natural products and antifungals were up to 8 times and 4 times higher than their MFC values, respectively. Tese results showed that the bioflm was more resistant to antimicrobial agents than planktonic cells, and this could be explained by the limited difusion of antimicrobial agents through the bioflm matrix or the lower growth rate of cells in the bioflm [6,36]. Tese results corroborated those reported earlier [14,24].…”
Section: Discussionsupporting
confidence: 84%
“… 34 Agreeably, there is scientific research on the interactions of antibiotics such as synergy, additivity, indifference, and antagonism, but not much is known about the interactions of antibiotics with the innate immune components. 35 , 36 …”
Section: Way Forward: Emerging Strategies For Tackling Antibiotic Res...mentioning
confidence: 99%
“…34 Agreeably, there is scientific research on the interactions of antibiotics such as synergy, additivity, indifference, and antagonism, but not much is known about the interactions of antibiotics with the innate immune components. 35,36 Although the direct in vitro mechanism of action of an antibiotic is thought to be the driving force behind its antimicrobial efficacy, additional antibiotic effects on bacteria have been linked to better host immunological activities and immune optimization. 37 This includes the ability of antibiotics to affect virulence factors and other immune mechanisms that can modulate host response.…”
Section: Immuno-antibiotics As An Alternativementioning
confidence: 99%
See 1 more Smart Citation
“…AMR has been a major concern because of the dramatic increase and huge challenge to the effective treatment of serious infections that are resistant to available antibiotics (Economou and Gousia, 2015). Additionally, the overuse/abuse of antibiotics in humans and food animals has resulted in the global dissemination of multidrug-resistant (MDR) bacteria and resistance genes, which are recently considered emerging contaminants for the environment (Abd El-Aziz et al, 2021;Ma et al, 2021;Saber et al, 2022;Xu et al, 2022). Moreover, the dissemination of MDR bacteria to human and animal food is facilitated by the application of animal manure in agriculture (Zalewska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%